Revitalizing Communal Piety Through Heutagogy: Local Wisdom and Leadership Development among New Muhammadiyah Members with CBPR - Afna, Mauloeddin (JAWAB: Journal of Asian World and Islamic Behavior Journal of Asian World and Islamic Behavior, 2023)
This article focused on a participatory action research that aimed to develop leadership characteristics among middle-ranged members of the Muhammadiyah organization in Kota Langsa. The study utilized the heutagogy paradigm, which emphasized self-determined learning and a holistic framework for nurturing leadership attitudes, engagement, and power. This approach was rooted in humanistic and constructivist principles that sought to cultivate the potential traits of the members. Throughout the research treatment, the members’ mindsets and lives were influenced, aligning them with the challenges confronted by the community and education in the 21st century. The study employed a design based on community-based participatory research (CBPR) of the participatory action research (PAR) design to engage the members in interactive processes and enhance their leadership capabilities. The findings underscored the significance of CBPR and the paradigmatic approach in validating members’ experiences in leading, managing, and organizing, thereby benefiting themselves, their families, and the community as a whole.